Exploring the Possibilities of Developing Sport Tourism in Linzi - Cui, Lihe (2009)
Though the concept of sport tourism has been applied to various products and services in a number of destinations, such as the USA and the UK, it is still a relatively new area for China tourism market. Sport tourism destination researches are mainly based on western countries with advanced developed competing sport industry and history and the feasibility of sport tourism based on a destination with cultural heritage sport resource has not well explored. This paper has two aims to achieve. First, it attempts to have a review of the theoretical literatures on sport tourism by previous researchers; second, it seeks to explore the possibilities to develop football based sport tourism in Linzi, the world football birthplace, which has been confirmed in 2004 by FIFA. The findings indicate that though there are challenges, football resource can be used to develop a new tourism sector.